2013
DOI: 10.2500/aap.2013.34.3698
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional analysis of pet-specific immunoglobulin E sensitization and allergic symptomatology and household pet keeping in a birth cohort population

Abstract: It is unknown whether family members with detectable specific immunoglobulin E (sIgE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“… 30 In fact, subjects with a pet allergy or those with family members with a pet allergy tended to keep pets less frequently, and the levels of pet allergens in their households were lower. 9 31 32 33 Whether pet owners allow their pets to enter their bedroom or a baby's room, and whether individuals regularly visit places where pets are kept or where pet allergens are pooled by pet allergen carriers ( e.g. , pet owners' clothes), such as schools or other public places, is also critical.…”
Section: Discussionmentioning
confidence: 99%
“… 30 In fact, subjects with a pet allergy or those with family members with a pet allergy tended to keep pets less frequently, and the levels of pet allergens in their households were lower. 9 31 32 33 Whether pet owners allow their pets to enter their bedroom or a baby's room, and whether individuals regularly visit places where pets are kept or where pet allergens are pooled by pet allergen carriers ( e.g. , pet owners' clothes), such as schools or other public places, is also critical.…”
Section: Discussionmentioning
confidence: 99%
“…Small children who need treatment for their allergic symptoms are likely to be tested for suspected allergens. Children may also be tested for allergic sensitization to make the decision to remove the pet from the home, albeit allergic diseases rarely lead to the removal of the pet or avoiding pet‐keeping . Children may also be tested in advance, before the pet is taken, to make sure that keeping it will be safe.…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, also some limitations that should be considered when interpreting our findings-in particular, the possibility of confounding by indication and reverse causation. Studies have demonstrated selective avoidance of pets, especially cats, among families with asthma or allergies 52,53 ; thus, it is likely that children at highest risk of developing allergies or asthma are also less likely to live with cats or dogs. Similarly, it is also possible that the development of early respiratory symptoms in the child (eg, infant wheeze) may result in the removal of pets from the home; this may be less common than avoidance, however.…”
Section: Strengths and Limitationsmentioning
confidence: 99%